A MaxSAT based approach for QoS cloud services. Issue 6 (1st November 2020) - Ait Wakrime, Abderrahim; Jabbour, Said; Hameurlain, Nabil
ABSTRACT: Web Services technologies are operated to build Software as a Service (SaaS) layer in the Cloud Computing. It happens that a single Web Service does not respond to customer's request. In this case, one needs to compose several distributed Web Services in order to achieve the customer's goal and allow interaction between heterogeneous applications. In this paper, a new approach for QoS Web Services problem is proposed. It is based on an original encoding using satisfiability problem. To minimise the composition and also take into account user preferences, an objective function is used leading to the known Maximum Satisfiability problem (MaxSAT). Such formulation is flexible and allows to introduce constraints in order to seek for specified Web Services Composition. Experimental evaluation on some generated instances shows the feasibility of our proposed approach.